(untitled) (Revista Rupturas, 2017)
The arrival of migrants and refugees often leads to debates about how far the “generosity” of the host country should reach with this population. For some sectors of these countries, this population not only makes abusive use of the public services, but also has a responsibility in the general deterioration of living conditions. This article discusses this topic that has been and continues to be present in the public opinion in Costa Rica, a country that receives migrant and refugee populations. Based on official sources and data from the National Survey of Households (2016) carried out by the National Institute for Statistics and Census – Instituto Nacional de Estadísticas y Censos – this article presents evidence that shows that the above arguments are not true. Faced with this approaches, empirical evidence is presented about how the foreign population contributes to the creation of wealth in the destination country, based on the contribution they make to the Gross Domestic Product and to the tax revenue. In times of nationalists and xenophobic discourses, a society like Costa Rica would have to stop wondering if it should integrate these populations and instead question itself: What is the best way to do it?